2015
DOI: 10.1111/ijs.12570
|View full text |Cite
|
Sign up to set email alerts
|

What's New in Stroke? Phase III Randomized Clinical Trials of 2012–2014

Abstract: The diversity of interventions, high-quality, and worldwide origins of recently published phase III randomized clinical trials reflects a vibrant international stroke research community. The current generation of stroke randomized clinical trials provides important guidance for stroke prevention and acute stroke care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…In this systematic review of 96 acute stroke therapeutic trials published between 2013 and 2020 in 9 high-impact journals, we found that a large proportion (41%) of trials were terminated before enrollment of their maximum planned sample size. This prevalence is similar to the estimate of 38% reported in a review of 34 phase 3 stroke RCTs published between 2012 and 2014 11 but higher than those reported in previous analyses of the general medical literature and cardiovascular-related RCTs, which ranged from 11% to 25%. 14,19–21 We also found higher utilization of prespecified stopping rules (59%), formal interim analyses (57%), and DSMBs (88%) than in previous reports conducted among a broader array of clinical trials.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In this systematic review of 96 acute stroke therapeutic trials published between 2013 and 2020 in 9 high-impact journals, we found that a large proportion (41%) of trials were terminated before enrollment of their maximum planned sample size. This prevalence is similar to the estimate of 38% reported in a review of 34 phase 3 stroke RCTs published between 2012 and 2014 11 but higher than those reported in previous analyses of the general medical literature and cardiovascular-related RCTs, which ranged from 11% to 25%. 14,19–21 We also found higher utilization of prespecified stopping rules (59%), formal interim analyses (57%), and DSMBs (88%) than in previous reports conducted among a broader array of clinical trials.…”
Section: Discussionsupporting
confidence: 85%
“…3,4 Other studies have described the underutilization and underreporting of design features intended to minimize bias and ensure early termination is appropriate, which include the use of prespecified interim statistical analyses, prespecified statistical stopping rules, and the actions and responsibilities of data and safety monitoring boards (DSMBs). 9,10 Although a 2015 study of stroke RCTs reported on the frequency of early termination, 11 a detailed assessment of the reasons for, reporting on, and impact of early termination among stroke trials is lacking. Thus, the primary objectives of this systematic review were to determine the prevalence of early termination among recently published acute stroke trials, document reasons for early termination, describe the use of DSMBs, prespecified interim analyses and stopping rules, and evaluate the quality of reporting on early termination and relevant trial features.…”
mentioning
confidence: 99%